2021
DOI: 10.1161/jaha.121.021126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcomes of Low‐Gradient Severe Aortic Stenosis—From the National Echo Database of Australia

Abstract: Background The prevalence and outcomes of the different subtypes of severe low‐gradient aortic stenosis (AS) in routine clinical cardiology practice have not been well characterized. Methods and Results Data were derived from the National Echocardiography Database of Australia. Of 192 060 adults (aged 62.8±17.8 [mean±SD] years) with native aortic valve profiling between 2000 and 2019, 12 013 (6.3%) had severe AS. Of these, 5601 patients (47%) had high‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Low gradient severe aortic stenosis may arise in patients with inherently small aortic annuli or low forward stroke volume due to poor systolic function, high arterial afterload, or small left ventricular chamber size [ 13 ]. In this study, looking at severe AS (isolated or mixed), 31% (218/704) had low-gradient severe AS, which is less than the most recent study in Australia showing that half of severe AS cases have low-gradient hemodynamics [ 14 ]. This is most likely due to less recognition and treatment for this confusing entity.…”
Section: Discussionmentioning
confidence: 83%
“…Low gradient severe aortic stenosis may arise in patients with inherently small aortic annuli or low forward stroke volume due to poor systolic function, high arterial afterload, or small left ventricular chamber size [ 13 ]. In this study, looking at severe AS (isolated or mixed), 31% (218/704) had low-gradient severe AS, which is less than the most recent study in Australia showing that half of severe AS cases have low-gradient hemodynamics [ 14 ]. This is most likely due to less recognition and treatment for this confusing entity.…”
Section: Discussionmentioning
confidence: 83%
“…It is important to note that conservative management of these patients has been associated with a dismal prognosis. Snir et al 9 reported that patients with classic low-flow low-gradient D2 AS with no procedural intervention had the highest 1-year and 5-year mortality compared with those with D1 and D3 AS at 30.5% and 72.9%, respectively. 9 Once patients develop symptomatic AS, mortality is >50% at 2 years unless valve replacement is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Snir et al 9 reported that patients with classic low-flow low-gradient D2 AS with no procedural intervention had the highest 1-year and 5-year mortality compared with those with D1 and D3 AS at 30.5% and 72.9%, respectively. 9 Once patients develop symptomatic AS, mortality is >50% at 2 years unless valve replacement is performed. 8 Long-term predictors of mortality for patients with low-flow/low-gradient AS include chronic obstructive pulmonary disease, residual moderate to severe mitral regurgitation, and anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that significant AS was not frequently observed in this study (0.90%). In fact, it was less frequently observed compared to the National Echocardiographic Database of Australia (NEDA) which reported severe AS in 6.3% [ 52 ]. The discrepancy may rely on the fact that NEDA represents a clinical registry, meaning they reported findings from echocardiograms performed for a clinical indication.…”
Section: Discussionmentioning
confidence: 99%